2019
DOI: 10.1038/s41598-019-39401-0
|View full text |Cite
|
Sign up to set email alerts
|

Mesalamine and azathioprine modulate junctional complexes and restore epithelial barrier function in intestinal inflammation

Abstract: Disruption of mucosal structure and barrier function contribute to the pathogenesis of inflammatory bowel disease (IBD). Efficacy of therapy in IBD is based on endoscopic mucosal healing, which occurs by a dynamic interplay of epithelial cell regeneration, migration and differentiation. Both mesalamine (5-ASA) and azathioprine (AZTP) promote this process through mechanisms not clearly understood. We examined molecular pathways implicated in epithelial barrier function that were altered by 5-ASA and AZTP. Parac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 48 publications
3
57
0
Order By: Relevance
“…Damaged epithelial cells interact with macrophages, which are the first responders to encounter gut microbes. Macrophages secrete pro-inflammatory mediators, such as IL-6 and TNF-α, which delay healing of colon epithelial cells (Khare et al, 2019). Safranal suppressed the production of IL-6 and TNF-α in colon tissue ( Figures 7A, B ).…”
Section: Resultsmentioning
confidence: 99%
“…Damaged epithelial cells interact with macrophages, which are the first responders to encounter gut microbes. Macrophages secrete pro-inflammatory mediators, such as IL-6 and TNF-α, which delay healing of colon epithelial cells (Khare et al, 2019). Safranal suppressed the production of IL-6 and TNF-α in colon tissue ( Figures 7A, B ).…”
Section: Resultsmentioning
confidence: 99%
“…However, our own unpublished data suggest that IBD medication does not affect cytokine production in pregnant IBD patients. 5-ASA and azathioprine are considered of low risk during pregnancy and therefore often used in clinical practice Studies investigating the effect of these treatments on the epithelial barrier function have indicated a positive effect in an intestinal organoids model [47]. Furthermore, 5-ASA was able to inhibit IFN-gamma induced impairment of the epithelial barrier [48].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory bowel syndrome and IBD cause frequent diarrhea, which reduces the quality of life . The kampo medicine KST has long been used for the treatment of abdominal pain caused by diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…97) exceeded 160 000 in 2013, and the number of IBD patients is increasing . Corticosteroids, 5‐aminosalicylic acid, immune modulators, such as thiopurine and methotrexate , biological drugs, and anti‐tumor necrosis factor (TNF) antibody are used for the treatment of IBD in both CD and UC patients. We previously reported that Swertia japonica extract and its main compound swertiamarine, and Atractylodes lancea rhizome extract and a volatile component β‐eudesmol stimulated gastric emptying and/or small intestine motility by inhibiting the dopamine D 2 and/or 5‐HT receptor .…”
Section: Introductionmentioning
confidence: 99%